Evidence Mapping of the Treatments for Breast Cancer–related Lymphedema. Issue 1 (18th January 2022) - Al-Sakkaf, Ali M.; Masia, Jaume; Auladell-Rispau, Ariadna; Shamardal, Aliaa I.; Vasconcello-Castillo, Luis; Sola, Ivan; Bonfill, Xavier
Abstract : Background: Women treated for breast cancer are facing a lifetime risk of developing lymphedema, which occurs in up to 40% of this population. There is a lack of evidence and limited knowledge regarding the treatment of breast cancer–related lymphedema (BCRL). The aim of this study was to identify, describe, and organize the currently available evidence in the treatment of BCRL. Methods: We conducted an evidence mapping review study according to the methodology proposed by Global Evidence Mapping. We performed a systematic search in Medline, Embase, Central (Cochrane), and Epistemonikos, from 2000–2020. We included studies about all treatment types for BCRL, including surgical and nonsurgical treatment. Results were summarized in narrative and tabular forms. Results: A total of 240 studies were included in this mapping review, distributed as follows: 147 experimental studies [102 randomized clinical trials (RCTs) and 45 quasi-experimental clinical trials], 48 observational studies (34 prospective and 14 retrospective studies), and 45 systematic reviews (17 of them with metanalysis). Most of the RCTs were on nonsurgical interventions. Only two RCTs addressed surgical intervention. Conclusions: In the last 20 years, there were an average of 12 publications per year on the treatment of BCRL. Recently this lack of attention has been partially corrected, as the majority were published in the past 5 years. However, most of them were on nonsurgical interventions. Well-designed RCTs on surgery are needed to measure the effectiveness of the applied interventions.